Peranan Kecerdasan Spiritual dalam Meningkatkan Motivasi Belajar Siswa - Irawan, Vaesol Wahyu Eka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2019)
Saturation of learning can strike students if they have lost motivation and lose consolidation of one particular skill level before the student reaches the next skill level. In addition, saturation can also occur because the learning process of students has reached the limits of physical abilities, because of boredom (boring) and fatigue (fatigue). Students' fatigue can be categorized into three types, namely: 1) student's sensory fatigue; 2) students' physical fatigue; 3) students' mental fatigue. Among the three types of fatigue, mental fatigue was seen as the main factor causing the emergence of learning saturation. Motivation as anfactor inner functions to cause, underlie, direct the act of learning. Motivation is one of the spiritual factors of students who are generally seen as more essential which can affect the quantity and quality of student learning. This means that motivation can determine the good or not in achieving the goal so that the strong weakness of one's learning motivation also influences its success. A person who learns with strong motivation, will carry out all his learning activities seriously, full of passion or enthusiasm, actively trying to read books to improve his performance to solve his problem, seeming persistent not to give up. Conversely, learning with weak motivation, attention is not focused on the lesson, does not want to do tasks related to the lesson, indifferent, easily discouraged, lazy, like to disturb the class.